Novel biotechnological platform based on baculovirus occlusion bodies carrying Babesia bovis small antigenic peptides for the design of a diagnostic enzyme-linked immunosorbent assay (ELISA) - Lopez, Maria Gabriela (2018)
Baculoviruses are large DNA virus of insects principally employed in recombinant protein expression. Its ability to form occlusion bodies (OBs), which are composed mainly of polyhedrin protein (POLH), makes them biotechnologically attractive, as these crystals (polyhedra) can incorporate foreign peptides and can be easily isolated. On the other hand, peptide microarrays allow rapid and inexpensive high-throughput serological screening of new candidates to be incorporated to OBs. To integrate these 2 biotechnological approaches, we worked on Babesia bovis, one of the causative agents of bovine babesiosis. Current molecular diagnosis of infection with B. bovis includes enzyme-linked immunosorbent assay (ELISA) techniques, which use merozoite lysate obtained from infected bovine erythrocytes. However, it is important to produce recombinant antigens that replace the use of crude antigens. Here, we describe a new biotechnological platform for the design of indirect ELISAs based on 5 antigenic peptides of 15 amino acid residues of B. bovis (ApBb), selected from a peptide microarray and expressed as a fusion to POLH. An Sf9POLHE44G packaging cell line infected with recombinant baculoviruses carrying POLH-ApBb fusions yielded higher levels of chimeric polyhedra, highlighting the advantage of a trans-contribution of a mutant copy of polyhedrin. Finally, the use of dissolved recombinant polyhedra as antigens was successful in an ELISA assay, as B. bovis-positive sera recognized the fusion POLH-ApBb. Thus, the use of this platform resulted in a promising alternative for molecular diagnosis of relevant infectious diseases.